A d-peptide-based oral nanotherapeutic modulates the PD-1/PD-L1 interaction for tumor immunotherapy - Liu, Dan; Wang, Jingmei; You, Weiming; Ma, Fang; Sun, Qi; She, Junjun; He, Wangxiao; Yang, Guang (Frontiers in Immunology, 2023)
Background: PD-1/PD-L1 immune checkpoint inhibitors are currently the most commonly utilized agents in clinical practice, which elicit an immunostimulatory response to combat malignancies. However, all these inhibitors are currently administered via injection using antibody-based therapies, while there is a growing need for oral alternatives.Methods: This study has developed and synthesized exosome-wrapped gold-peptidenanocomplexes with low immunogenicity, which can target PD-L1 and activate anti-tumor immunity in vivo through oral absorption. The Super PDL1 exo was characterized by TEM electron microscopy, DLS, FTIR, XPS and gel silver staining. The transmembrane ability of Super PDL1 exo was evaluated by flow cytometry and immunofluorescence. Cell viability was determined using the CCK-8 assay. Elisa experiments were conducted to detect serum and tissue inflammatory factors, as well as serum biochemical indicators. Tissue sections were stained with H&E for the evaluation of Super PDL1 exo 's safety. An MC38 colon cancer model was established in immunocompetent C56BL/6 mice to evaluate the effects of Super PDL1 exo on tumor growth in vivo. IHC staining was performed to detect cytotoxicity factors such as perforin and granzymes.Results: Firstly, Super PDL1 was successfully synthesized, and milk exosome membranes were encapsulated onto a through ultrasound, repeated freeze-thaw cycles, and extrusion, resulting in the synthesis of Super PDL1 exo . Multiple characterization results confirmed the successful synthesis of Super PDL1 exo nanoparticles. Furthermore, our data demonstrated that Super PDL1 exo exhibited excellent colloidal stability and superior cell transmembrane ability. In vitro and in vivo experiments revealed that Super PDL1 exo did not cause damage to multiple systemic organs, demonstrating its good biocompatibility. Finally, in the MC38 colon cancer mouse model, it was discovered that Super PDL1 exo could inhibit the progression of colon cancer, and this tumor-suppressive effect was mediated through the activation of tumor-specific cytotoxic T lymphocytes (CTLs)-related immune responses.This study has successfully designed and synthesized an oral nanotherapeutic, Super PDL1 exo , which demonstrates small particle size, excellent colloidal stability, transmembrane ability in tumor cells, and biocompatibility. In vivo experiments have shown that it effectively activates T-cell immunity and exerts anti-tumor effects.